Decision Support System for Bankruptcy Risk Assessment of the Enterprise - Telipenko E. V. Elena Viktorovna; Zakharova A. A. Aleksandra Aleksandrovna; Sopova S. P. Svetlana Petrovna; Minkov S. L. Sergey Leonidovich; Dzhamansariev N. B. Nurbek Bakytbekovich (2016, 2016)
Title screen